Behavior of deep level defects on voltage-induced stress of Cu(In,Ga)Se-2 solar cells - Lee, D. W.; Cho, S. E.; Jeong, J. H.; Cho, H. Y. (ELSEVIER SCIENCE SA, 2015)
The behavior of deep level defects by a voltage-induced stress for CuInGaSe2 (CIGS) solar cells has been investigated. CIGS solar cells were used with standard structures which are Al-doped ZnO/i-ZnO/CdS/CIGSe(2)/Mo on soda lime glass, and that resulted in conversion efficiencies as high as 16%. The samples with the same structure were isothermally stressed at 100 degrees C under the reverse voltages. The voltage-induced stressing in CIGS samples causes a decrease in the carrier density and conversion efficiency. To investigate the behavior of deep level defects in the stressed CIGS cells, photo-induced current transient spectroscopy was utilized, and normally 3 deep level defects (including 2 hole traps and 1 electron trap) were found to be located at 0.18 eV and 0.29 eV above the valence band maximum(and 0.36 eV below the conduction band). In voltage-induced cells, especially, it was found that the decrease of the hole carrier density could be responsible for the increase of the 0.29 eV defect, which is known to be observed in less efficient CIGS solar cells. And the carrier density and the defects are reversible at least to a large extent by resting at room-temperature without the bias voltage. From optical capture kinetics in photo-induced current transient spectroscopy measurement, the types of defects could be distinguished into the isolated point defect and the extended defect. In this work, it is suggested that the increase of the 0.29 eV defect by voltage-induced stress could be due to electrical activation accompanied by a loss of positive ion species and the activated defect gives rise to reduction of the carrier density. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: CURRENT TRANSIENT SPECTROSCOPY; RESISTIVITY BULK MATERIALS; HIGH-ENERGY ELECTRON; GENERATION; TRAPS